Estimación del índice de mérito total del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia Aláquez. - Quistial Arcos, Monserrat Carolina (2023)
The lack of a program for genetic improvement in dairy cattle in the Aláquez parish located in the Northwest of Latacunga city, in the province of Cotopaxi, has caused small and medium producers to choose to carry out the same practices used years ago, which consisted of unknowingly selecting a player waiting for years to see the profitability of their offspring. That is why this research seeks to make small and medium producers aware to keep proper genealogical or productive records of their animals to implement a genetic improvement program based on the area conditions. The main objective of the research is to estimate the total merit index of each animal tested to consider them as breeders and thus obtain economically efficient animals. Therefore, to maximize the profitability of livestock production in the Aláquez, parish it is necessary to select animals that have functional characteristics that allow reducing the cost of production, by using the available resources efficiently. 259 animals distributed in San Marcos, Tandalivi, San Antonio, and El Tejar neighborhoods were assessed. Of them 230 were female and 29 are male. The Economic value was estimated using attributed data. The food bill was $595.50 per month with a selling cost per liter of milk of 43 cents, with a milk production cost of 17 cents per liter of milk and a benefit-cost of $555 per month on average per member. The estimation of the genetic value in the animals of the project was made by the BLUP where it was identified that the best animal to transmit characteristics in terms of GDP was the Tatiana cow with an estimate of + 437 gr up todate, as for milk production was a goat with + 1655 kg for breastfeeding and for the density was Nevis with a maximum value of 0.24. For the selection response, it was obtained that the best animals were for GDP Tatiana with 775 gr, Goat milk production with 5367 kg, and for Snow density with 1.27 gr/ml. Estimating the genetic value of dairy cattle is a powerful and essential tool for the genetic improvement of the population. It contributes to increasing productivity, improving health and endurance, reducing costs, and focusing effort on specific characteristics, which benefits both producers and the dairy industry in general. However, it is important to constantly monitor, maintain a reliable database and use up-to-date genetic analysis techniques to obtain accurate and effective results.